Review: Recent status of Selaginella (Selaginellaceae) research in Nusantara (Biodiversitas Journal of Biological Diversity, 2011)
Setyawan AD. 2011. Recent status of Selaginella (Selaginellaceae) research in Nusantara. Biodiversitas 12: 112-124. Selaginella Pal. Beauv. (Selaginellaceae Reichb.) is a cosmopolitan genus that grows in tropical and temperate regions. Some species of Selaginella have widely distribution and tend to be invasive, but the others are endemics or even, according to IUCN criteria, endangered. Nusantara or Malesia (Malay Archipelago) is the most complex biogeographic region and rich in biodiversity. It is one of the biodiversity hotspotof Selaginella, whereas about 200 species of 700-750 species are exist. Selaginella has been survived for 440 mya without any significant morphological modification, but extinction of tree-shaped species. Selaginella have similar morphological characteristics, particularly having heterospore form and loose strobili; and is classified as one genus and one family. However, individual species has high morphological variation caused by different edaphic and climatic factors. Genetic studies indicate high polymorphism among Selaginella species. Selaginella had been used as complementary and alternative medicines treated to postpartum, menstrual disorder, wound, etc. Biflavonoid – the main secondary metabolites – gives this benefit and is especially used as anti oxidant, anti-inflammatory, and anti cancer in modern pharmaceutical industry. The other metabolites, trehalose, potentially act as molecular stabilizer in biological based industry. Metabolite profiles can also be used to identify Selaginella by its species, time and harvest age, and locations. Since most of Selaginella grows on moist, organically rich, and well drained soils, which is vulnerable to forest degradation and global warming, it needs more conservation priority. Biosystematics and ethnobotanical researches of Nusantara Selaginella is needed to expand taxonomic status and bioprospecting of this bioresources.
Keywords: biosystematics, ethnobotany, research, Nusantara, Selaginella.